HUBUNGAN PENGETAHUAN, SIKAP DAN PENDIDIKAN IBU TERHADAP PEMBERIAN MP-ASI PADA BALITA 6 – 24 BULAN DI DESA BINANGGA KECAMATAN MARAWOLA KABUPATEN SIGI - Arfiah Arfiah (Sekolah Tinggi Pariwisata Mataram, 2019)
Provision of MP-ASI in infants is one of the efforts to meet the nutritional needs of infants so that the baby can achieve optimal growth. Provision of MP-ASI in infants is the provision of foods or beverages containing nutrients in infants aged 6-24 months to meet the nutritional needs after exclusive breastfeeding. Factors that affect the provision of MP-ASI in children aged 6 to 24 months of maternal education, mother knowledge, mother attitude, and sources of information about the practice of giving breast milk. In theory, knowledge will determine a person's behavior. This study aims to analyze the relationship of knowledge, attitudes and education of mothers to the provision of MP-ASI in toddlers 6 - 24 months in Binangga Village Marawola District Sigi District. The type of this research is analytic research with cross sectional approach. The population in this study were all mothers who had 6-24 months children in Binangga Village Marawola District Sigi Regency amounted to 104 people. The sample size is calculated based on the proportion estimation with the sample number of 50 people. Research data were analyzed using univariate and bivariate analysis. The result of the research shows that from 50 respondents most are mothers who have good knowledge about the provision of complementary foods of breastfeeding in children under five toddlers 6 to 24 months 76.0%, have attitude accept 76.0%, low education is 52% . Result of Fisher's Exact test of knowledge, attitudes obtained p value = 0.000 and Chi Square test results p = 0.003 value (< 0.05), this means statistically there is a statistically significant relationship between knowledge, attitude and education of mother with accuracy provision of MP-ASI. Conclusion: there is a meaningful relationship between knowledge, attitude and education of mother with the accuracy of giving of MP-ASI.